A Two-Tube Multiplex Reverse Transcription PCR Assay for Simultaneous Detection of Sixteen Human Respiratory Virus Types/Subtypes. (5th August 2013) - Li, Jin; Qi, Shunxiang; Zhang, Chen; Hu, Xiumei; Shen, Hongwei; Yang, Mengjie; Wang, Ji; Wang, Miao; Xu, Wenbo; Ma, Xuejun
Abstract : There is a need for the development of a rapid and sensitive diagnosis of respiratory viral pathogens. With an intended application in provincial Centers for Diseases Control and Prevention, in this study, we present a two-tube multiplex RT-PCR assay (two-tube assay) using automatic electrophoresis to simultaneously detect sixteen common respiratory viruses. The specificity and the sensitivity of the assay were tested. The assay could detect 20–200 copies per reaction when each viral type was assayed individually, 2000 copies with 9 premixed viral targets in the multiplexed assay in tube 1, and 200 copies with 8 premixed templates in tube 2. A total of 247 specimens were used to evaluate the two-tube assay, and the results were compared with those obtained from the Luminex xTAG RVP Fast assay. The discordant results were confirmed by sequencing or by the Seeplex RV15 ACE detection kit. There were no false positives, but six false negatives occurred with the two-tube assay. In conclusion, the two-tube assay is demonstrated to have great potential for routine surveillance of respiratory virus infection in China.